Microsoft Windows 98 resource kit (Microsoft P. RedmondUS, 1998)
Provides insights on installing, configuring and supporting Windows 98. Covers deployment and installation; system configuration; networking and intranets; internet and communication tools: system management and architecture. Includes glossary and electronic version of the book on CD.
Title discarded 2013-10-15. S. Barker